2018
DOI: 10.3389/fphys.2018.00760
|View full text |Cite
|
Sign up to set email alerts
|

Ion Channels in the Paraventricular Hypothalamic Nucleus (PVN); Emerging Diversity and Functional Roles

Abstract: The paraventricular nucleus of the hypothalamus (PVN) is critical for the regulation of homeostatic function. Although also important for endocrine regulation, it has been referred to as the “autonomic master controller.” The emerging consensus is that the PVN is a multifunctional nucleus, with autonomic roles including (but not limited to) coordination of cardiovascular, thermoregulatory, metabolic, circadian and stress responses. However, the cellular mechanisms underlying these multifunctional roles remain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 224 publications
(286 reference statements)
0
24
0
Order By: Relevance
“…The elimination of [Ca 2+ ] i elevation by removing extracellular Ca 2+ or blocking channels with Cd 2+ strongly indicates the involvement of one or more plasma membrane proteins. Both magno‐ and parvocellular neurones express L‐type Ca 2+ channels, and parvocellular neurones express T‐type Ca 2+ channels as well . Non‐neurosecretory parvocellular neurones have much larger T‐type Ca 2+ currents then neurosecretory parvocellular neurones, and these low threshold channels may be responsible for the [Ca 2+ ] i increase that we observe.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…The elimination of [Ca 2+ ] i elevation by removing extracellular Ca 2+ or blocking channels with Cd 2+ strongly indicates the involvement of one or more plasma membrane proteins. Both magno‐ and parvocellular neurones express L‐type Ca 2+ channels, and parvocellular neurones express T‐type Ca 2+ channels as well . Non‐neurosecretory parvocellular neurones have much larger T‐type Ca 2+ currents then neurosecretory parvocellular neurones, and these low threshold channels may be responsible for the [Ca 2+ ] i increase that we observe.…”
Section: Discussionmentioning
confidence: 60%
“…Because our cultures likely contain multiple types of PVN neurones, the differential expression of T‐type currents may also explain why only a subset of neurones increased [Ca 2+ ] i when exposed to NE or PE. In addition, Ca 2+ permeable transient receptor potential cation (TRP) channels and NMDA receptors are also present in the PVN, and may contribute to [Ca 2+ ] i influx upon depolarisation or phosphorylation. Although Cd 2+ is a prototypical voltage‐dependent Ca 2+ channel (VDCC) blocker, it has also been shown to block TRP channels .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This in turn increases the activation of Ca 2+ -activated K + channels and enables the feedback loop to continue. We were able to simulate this numerically in the case of the PVN neurones ( Feetham et al, 2018 ). We demonstrated that the Ca 2+ elevation appears to be mediated by TRPV4 channels, and that the small-conductance Ca 2+ -activated K + channels (SK channels) mediate a hyperpolarization that both increases intracellular Ca 2+ and decreases their action potential firing frequency ( Feetham et al, 2015b ).…”
Section: Biological Sensingmentioning
confidence: 99%
“…1c). Therefore, the distribution of tdTomato-positive neurons in the PVH were assessed according to the subdivisions described in the previous report 21 (Fig. 1e).…”
Section: Fasting-refeeding Activates a Subset Of Neurons In The Compamentioning
confidence: 99%